2016
DOI: 10.1002/fsn3.449
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive phytochemicals in an aqueous extract of the leaves of Talinum triangulare

Abstract: An aqueous leaf extract of Talinum triangulare was screened for the presence of bioactive molecules, using gas chromatography coupled with pulse and flame ionization detectors. It had high carotenoids; moderate benzoic acid derivatives, hydroxycinnamates and flavonoids; and low terpenes, alkaloids, phytosterols, allicins, glycosides, saponins, and lignans contents. Ten known carotenoids (mainly 50.42% carotene and 33.30% lycopene), nine benzoic acid derivatives (mainly 84.63% ferulic acid and 11.92% vanillic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…No β-carotene content was recorded for boiled and blanched leaf samples. The result in Table 11 is in agreement with Ikewuchiet al, (26), Idris et al, (27), and Joshua et al, (28) who reported a decline in the ash, lipid, and fiber contents of Talinum triangulare. They also reported a similar increase in the carbohydrate and protein contents of leaf samples dried under the shade.…”
Section: Discussionsupporting
confidence: 89%
“…No β-carotene content was recorded for boiled and blanched leaf samples. The result in Table 11 is in agreement with Ikewuchiet al, (26), Idris et al, (27), and Joshua et al, (28) who reported a decline in the ash, lipid, and fiber contents of Talinum triangulare. They also reported a similar increase in the carbohydrate and protein contents of leaf samples dried under the shade.…”
Section: Discussionsupporting
confidence: 89%
“…Crinamidine is an alkaloid obtained from Crinum latifolium and Talinum triangulare. In Chinese ethnomedicine, the antiviral and antitumor properties of the extract of Crinum latifolium has been reported [84,85]. Sinensetin can be found in orange (Citrus sinensis)…”
Section: Resultsmentioning
confidence: 99%
“…Suas folhas contêm uma quantidade considerável de ácidos graxos de cadeia média. 52,53 O destaque de T. subulata também está relacionado ao seu potencial bioativo, principalmente compostos fenólicos e flavonoides, atestando algumas de suas atividades antioxidantes e anti-inflamatórias citadas em estudos etnobotânicos. 54 É importante mencionar que a ação dos compostos bioativos nos alimentos depende da ingestão nas quantidades certas.…”
Section: Pereskia Aculeataunclassified